2007
DOI: 10.1093/humrep/dem088
|View full text |Cite
|
Sign up to set email alerts
|

Fertility-preserving treatment with progestin, and pathological criteria to predict responses, in young women with endometrial cancer

Abstract: Patients with an initial PR can obtain CR after further treatment, and the PgR may be useful in predicting CR to fertility-preserving treatment in young women with endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 19 publications
3
96
1
Order By: Relevance
“…These conflicting clinical findings may be because of tumor heterogeneity, resulting from genetic alterations in addition to PTEN loss. The expression of PR in endometrial cancer specimens correlates with a positive response to progesterone therapy (25,37). In our in vivo model, differential expression of epithelial PR was observed in AKT vs. PTEN-initiated tumors.…”
Section: Discussionmentioning
confidence: 61%
“…These conflicting clinical findings may be because of tumor heterogeneity, resulting from genetic alterations in addition to PTEN loss. The expression of PR in endometrial cancer specimens correlates with a positive response to progesterone therapy (25,37). In our in vivo model, differential expression of epithelial PR was observed in AKT vs. PTEN-initiated tumors.…”
Section: Discussionmentioning
confidence: 61%
“…Studies at various institutions have reported the results of fertility-sparing treatment for EC using progesterone preparations (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). However, as the number of cases have been low, the efficacy of such treatment has yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…These cases were mostly thought to be independent primary or concurrent ovarian endometrioid adenocarcinoma based on histological findings showing that both lesions were very early stage and were rarely confirmed by a heterozygous pattern at the human androgen receptor gene locus. It is of note that Huang et al found similar microscopic patterns, immunohistochemical profiles, and DNA ploidy in a small ovarian lesion of 2×2 mm 2 compared to a primary endometrial lesion [9,11,[14][15][16].…”
Section: Discussionmentioning
confidence: 86%
“…Cases in which extrauterine metastasis occurred during conservative therapy, such as those reported by Imai et al and Ota et al, were also excluded because such cases can be treated by standard surgery. Thus, 13 cases of extrauterine recurrence after temporary remission are listed in Table 2 [3,[8][9][10][11][12][13][14]. Six of these cases had ovarian lesions as the extrauterine site.…”
Section: Discussionmentioning
confidence: 99%